(untitled) (Washington, D.C., 2010)
The Eco2 Cities approach is a point of departure for cities that would like to reap the many benefits of ecological and economic sustainability. It provides an analytical and operational framework that offers strategic guidance to cities on sustainable and integrated urban development. At the same time case studies are used throughout the book to provide a matter-of-fact and ground-level perspective. The Eco2 framework is flexible and easily customized to the context of each country or city. Based on the particular circumstances and the development priorities of a city – the application of the framework can contribute to the development of a unique action plan or roadmap in each case. This action plan can be triggered through catalyst projects.
Keywords: Sustainable development,Urbanization,Đô thị hóa,Phát triển bền vững,Urbanization,Đô thị hóa; Environmental aspects,Khía cạnh kinh tế,Economic aspects,Khía cạnh môi trường; Developing countries,Developing countries,Nước đang phát triển,Nước đang phát triển,Developing countries,Nước đang phát triển